Сумма эффективных температур весеннего развития зародыша дубовой листовертки зеленой - Самарин, В.Ф. (Вестник зоологии, 1968)
The closest as to the value, sums of temperatures at which the Tortrix viridana L. caterpillar going out was observed during eight years, were obtained when taking the initial readings from the temperature above +3, +4° C. When taking the initial readings above or below the mentioned temperature the sums of the years considerably differ between themselves. Thus an average sum of the effective temperatures for Tortrix viridana L. was determined in 173° C, and a lower threshold of development was +3° C. In years with first autumn frosts, after which a stable rise in temperature came, a sum of the effective temperatures of embryo development in spring period was lower than the usual one. In such years, probably the processes of development proceeding, as a rule, in spring, occur partially in autumn, as a result of which the sum of the effective temperatures in spring period decreases.